Insights into the pharmacodynamics and pharmacokinetics of meldonium after exposure to acute high altitude - Liu, Fengying; Sui, Xin; Wang, Qian; Li, Jinglai; Yang, Weijie; Yang, Yi; Xiao, Zhenyu; Sun, Yangyang; Guo, Xiaoxuan; Yang, Xinyi; Yang, Jun; Wang, Yongan; et al. (Frontiers in Pharmacology, 2023)
Objective: Meldonium, a well-known cardioprotective drug, has been reported to be protective against pulmonary injury at high altitudes; however, the pharmacodynamics of meldonium in other vital organs under acute high-altitude injury are less investigated and the related pharmacokinetics have not been fully elucidated. Methods and Results: The present study examined the basic pharmacodynamics and pharmacokinetics (PK) in rat exposure to acute high-altitude hypoxia after intragastrical and intravenous pre-administration of meldonium. The results indicate that meldonium can improve acute hypoxia-induced pathological damage in brain and lung tissues, and restore blood biochemistry and routine blood index of heart, liver and kidney tissues under a simulated acute high-altitude environment. Furthermore, compared to the normoxia group, rats exposed to simulated high-altitude hypoxia and premedicated with intragastrical meldonium showed linear kinetics in the dose range of 25–100 mg/kg, with a significantly increase in the area under curve (AUC) and reduced clearance rate. No significant differences in these meldonium of PK parameters were observed with intravenous administration. Additionally, meldonium was involved in the regulation of succinic acid and 3-hydroxypropionic acid. Conclusion: These results will contribute to our understanding of the preclinical PK properties of meldonium and its acute high-altitude protective effects.